Hasimoto surfaces in Galilean space $$G_{3}$$ G 3 - M. Elzawy (Journal of the Egyptian Mathematical Society, 2021)
Abstract In this article Hasimoto surfaces in Galilean space $$G_{3}$$ G 3 will be considered, Gauss curvature (K) and Mean curvature (H) of Hasimoto surfaces $$χ =χ (s,t)$$ χ = χ ( s , t ) will be investigated, some characterization of s-curves and t-curves of Hasimoto surfaces in Galilean space $$G_{3}$$ G 3 will be introduced. Example of Hasimoto surfaces will be illustrated.